PREFERENSI PETANI TERHADAP KERAGAAN PADI VARIETAS UNGGUL BARU DI RAWA LEBAK TENGAHAN - Darsani, Yanti Rina; hairani, anna (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2020)
Introducing high yield varieties to farmers by demonstration plots is one of efforts to accelerate the adoption of these varieties. The objective of study was to determine the preferences of farmers on the characteristics of rice high yield varieties on medium freshwater swampland. The study was carried out on farmer's land at Hamayung village, Daha Utara subdistrict, Hulu Sungai Selatan regency in 2017. There were 20 selected farmers as samples by simple random sampling. Collected data were farmer characteristics and rice morphology that obtained by interviews with farmers using questionnaires and farmer observations on plant growth of 10 rice high yield varieties in the field before harvesting. The obtained data were tabulated, grouped and analyzed descriptively. The results showed that (1) the most preferred performance of plants was plant age, panicle length, plant type, grain shape and plant height and (2) Mekongga, Inpari 30, Inpara 6, Inpari 9, Inpari 17, Ciherang and Inpara 8 were the preferred variety (from the most preferred order) varieties based on their agromorphology.